The Influence of It Governance and It Capability on The Performance of Private Higher Education Institutions: The Mediation Role of Performance Management Systems - Utami, Tiyas Puji; Pratolo, Suryo (Universitas Swadaya Gunung Jati, 2023)
This study examines the effect of information technology (IT) governance and IT capability on the organizational performance of private Higher Education Institutions (HEI) with a performance management system as a mediating variable. This quantitative study uses primary data from questionnaires distributed to respondents online. Respondents in this study were 270 management and IT management of private universities on the island of Sumatra. This study used a sample of 90 private HEIs. Furthermore, the data was processed using Partial Least Square (PLS) technique. The results are that the performance management system partially mediates IT governance with organizational performance, while IT capability mediates fully with organizational performance. IT capabilities can encourage organizational performance through a good performance management system. Theoretically, it contributes to implementing technological resources mobilized in the performance management system to improve college performance. College management should consider developing technology and performance measurement systems to achieve sustainable competitive advantage.